2016
DOI: 10.1038/nature20567
|View full text |Cite
|
Sign up to set email alerts
|

Receptor usage dictates HIV-1 restriction by human TRIM5α in dendritic cell subsets

Abstract: The most prevalent route of HIV-1 infection is across mucosal tissues after sexual contact. Langerhans cells (LCs) belong to the subset of dendritic cells (DCs) that line the mucosal epithelia of vagina and foreskin and have the ability to sense and induce immunity to invading pathogens. Anatomical and functional characteristics make LCs one of the primary targets of HIV-1 infection. Notably, LCs form a protective barrier against HIV-1 infection and transmission. LCs restrict HIV-1 infection through the captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
186
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(192 citation statements)
references
References 37 publications
4
186
0
2
Order By: Relevance
“…This observation is consistent with previous studies showing that innate responses in the mucosa immediately following infection are inducing a potent antiviral state through the up-regulation of ISGs, many of which have anti-HIV-1 activity (63,64,(66)(67)(68)(69)(70)(71)(72)(73). All IFN subtypes signal through the same heterodimeric receptor (30), but differences in receptor binding and/or downstream signal transduction pathways are thought to be responsible for IFN subtype-specific biological effects (74)(75)(76)(77).…”
Section: Discussionsupporting
confidence: 80%
“…This observation is consistent with previous studies showing that innate responses in the mucosa immediately following infection are inducing a potent antiviral state through the up-regulation of ISGs, many of which have anti-HIV-1 activity (63,64,(66)(67)(68)(69)(70)(71)(72)(73). All IFN subtypes signal through the same heterodimeric receptor (30), but differences in receptor binding and/or downstream signal transduction pathways are thought to be responsible for IFN subtype-specific biological effects (74)(75)(76)(77).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, one of the main migratory DC subsets, the CD103 + DCs does not seem to play a role on EBOV dissemination since we did not detect expression of viral GP in the surface of CD103 + DCs. Interestingly, there are substantial parallelisms between our study and a recent HIV report which indicated that productive infection of DC-SIGN + but not langerin + DCs by HIV depended on the C-type lectin receptor usage25. Since CD103 + DCs express langerin26 but not DC-SIGN, it seems worthwhile to determine whether EBOV can actually infect CD103 + DCs or rather whether the virus cannot replicate in these cells.…”
Section: Discussionsupporting
confidence: 77%
“…In Langerhans cells, which are dendritic immune skin cells, HIV was degraded by the restriction factor tripartite motif-containing protein 5α (TRIM5α) and its ability to regulate the assembly of autophagy activating complexes ( Fig. 5.4) [110].…”
Section: Autophagy-mediated Restriction Of Viral Replicationmentioning
confidence: 99%